Evaluation of genotoxicity related to oral methylene blue chromoendoscopy - Repici, Alessandro; Ciscato, Camilla; Wallace, Michael; Sharma, Prateek; Anderloni, Andrea; Carrara, Silvia; Di Leo, Milena; Hassan, Cesare (Endoscopy, 2018)
Background An oral formulation of methylene blue with colonic delivery (MB-MMX) has been developed to increase detection of colorectal polys during colonoscopy. Traditionally, there have been safety concerns regarding DNA damage when methylene blue is exposed to white light. The aim of this study was to evaluate DNA damage in colonic mucosa after MB-MMX chromoendoscopy.Methods This was an open-label phase II safety study to assess for genotoxicity on colorectal biopsies of patients undergoing two sequential colonoscopies before and after an oral dose of 200 mg MB-MMX added to their bowel prep. Analysis of a biomarker of double-stranded DNA breaks, γH2AX, was performed on biopsy specimens.Results Ten patients were included in the study. The mean expression of γH2AX ± 95 % confidence intervals of the 50 biopsies before and after MB-MMX administration were 0.58 ± 0.08 and 0.62 ± 0.09, respectively (P = 0.24). None of the analyzed samples showed excess positive γH2AX expression, confirming the absence of DNA damage on biopsies after methylene blue exposure. No deaths or serious adverse events occurred.Conclusions An oral dose of 200 mg of MB-MMX did not result in any detectable DNA damage.